Compassion Scale: factor structure and scale validation in Hong Kong adolescents - Ngai, Steven Sek-yum; Cheung, Chau-kiu; Ng, Yuen-hang; Guo, Hao-yi; Du, Han-lei; Chen, Chen; Wong, Laing-ming; Zhou, Qiu-shi; Pang, Wing-tsam (Frontiers in Psychology, 2025)
IntroductionThis study aimed to validate the 16-item Compassion Scale (CS) for use with Hong Kong adolescents. 1,193 secondary school students in grades 7 to 11 (M = 13.80 years, 43.3% female) completed the questionnaire survey.MethodsWe used EFA and CFA to examine the factor structure of the CS and assessed its convergent and discriminant validity through CR, AVE, AIC, and BIC calculations. We also evaluated the concurrent validity by analysing partial correlations between the CS and its subscales with social connectedness and self-efficacy. In addition, we employed multigroup analysis to determine the model fit of the CS across demographic subgroups.ResultsFactor analyses showed a three-factor structure combining mindfulness and kindness into one factor that we named benevolence, together with common humanity and indifference. Satisfactory model fit was found in different subgroups across age, gender, grade, and school type. Findings suggested that girls, on average, showed a higher level of compassionate concern for others than boys, and younger adolescents were more compassionate than their older counterparts. The CS and its subscales were significantly and positively correlated with social connectedness and self-efficacy, supporting concurrent validity.DiscussionThe findings signify the unique sociocultural context in Hong Kong, which is deeply affected by Chinese traditions, Western individualism, and neoliberal ideals. Overall, the study provides robust support for the CS as a reliable and valid measure for cross-cultural research on compassion and yields evidence-based implications for compassion interventions.